Pengaruh Lingkungan Eksternal, Internal dan Etika Bisnis terhadap Kemitraan Usaha serta Implikasinya pada Kinerja Usaha Kecil - Tatang Suryana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2014)
This research is expected to contribute to development economics in particular, external and internal environment, business ethics, business partnership, performance small enterprises, strategic management, marketing management, human resource management, and economic in general.The study was conducted by using descriptive and inductive methods, namely collecting, presenting and analyzing and testing hypotheses, and making inferences and suggestions. Research conducted on batik cap small businesses in West Java with a sample size of 116 companies through simple random sampling technique proportionally. The method of analysis using structural equation model (SEM). This research, obtained some conclusions as follows: 1) The external environment has shown a fairly good level categories and need to be considered regarding the certainty of government in setting the wage system. Internal environment has shown a good level categories, but keep in mind the human resource owned by the company. Business ethics is a good show category, but still need to acquisition capitalization companies generally obtained directly.2) Partnership shows a fairly good level category, but it should be noted again the level of profits that have not been in accordance with the company's goals. 3) Performance of small businesses showed a fairly good level category, but should be considered companies are always trying to acquire new customers. 4) Based on SEM analysis showed that the external environment, internal environment, and business ethics simultaneously positive and significant impact on the partnership variable of 64.6%. External environment partially positive and significant impact to business partnerships of 15.51%.Internal environment positive and significant impact to business partnerships of 28.73%.Business ethics positive and significant effect to business partnerships of 20.30%. 5) Business Partnership positive and significant impact to Small enterprises Performance of 84.3%.